A study of paper and video projected displays to shorten assembly operations in assemble-to-order systems identification and comparison of assembly time components and their relationships - Calamlam, Abel M. (2013)
This thesis identifies and compares the components of Assembly Time and the relationships that exist among them to shorten the assembly process. The Assemble-to-Order (ATO) strategy has been widely used by business organizations to quickly and cost-effectively provide products that are customized to certain extent. Here, the major concern in delivering customer orders id the Assembly Time of products. The main objective of this research is to shorten the assembly process. The problem, however, is the insufficiency of knowledge regarding what comprises the Assembly Time. The conceptual framework of the study suggests that the assembly process can be shortened by identifying the components of the total time, as well as the relationships among the components, and determining the effects of distance between the worker and the visual display. As the research states, the reduction of 25% in the distance between the visual display and the assembler shortens the Assembly Time by at least 20%. There are two (2) methods used for acquiring information from the experiments (1) Real Time and (2) Post Experiment investigations. The two (2) experimental setups use the NAC EMR-9¬© Eye Tracker which is installed on the heads of the respondents to measure the amount of time the eyes focus on a specific area of interest. The research has found that Reaction Time, Gaze Time and Hard Work Time are the components of the Assembly Time. There are also two relationships identified: (1) sequential and (2) overlapping. The results show significant improvements in the Assembly Time when the assemblers use the video projected displays than the paper displays. The research concludes that the distance reductions results in more processing of overlaps for paper displays and video projected displays. There is a 19.04% and 26.25% differences in overlaps for the paper and video projected displays, respectively.
Thesis (M.S. Industrial Engineering)--University of the Philippines, Diliman
Keywords: Assembly-line methods